Kounis syndrome following moxifloxacin and deflazacort administration - Eugenia Morello; Silvia Bosio; Sibilla Anna Teresa Salvadeo (European Journal of Case Reports in Internal Medicine)
Kounis syndrome (KS), characterized by the simultaneous occurrence of acute coronary syndrome (ACS) and allergic reactions, can be triggered by a range of factors and drugs. We report on the case of a patient who arrived at our emergency department (ED) with symptoms of an allergic reaction after taking moxifloxacin and deflazacort orally. In the ED, the patient experienced a 5-minute episode of oppressive chest pain. A 12-lead electrocardiogram (ECG) was registered, and elevated troponin levels were detected in the blood, suggesting myocardial damage. The patient was admitted to the internal medicine department for observation, and a second 12-lead ECG demonstrated a significant variation in the repolarization pattern. The day after, a coronary angiography revealed no significant stenosis, thus supporting, along with elevated serum tryptase levels, the diagnosis of KS. This case report highlights two potential triggers for KS and emphasizes the critical importance of early recognition and prompt treatment of KS.